Introduction - Jo Mynard; Dominique Vola Ambinintsoa; Eduardo Castro (Studies in Self-Access Learning Journal)
Welcome to this issue of SiSAL journal, which consists of ten papers in the main section, one review (edited by Hisako Yamashita), and one paper in the Ethnographies of Self-Access section. We are delighted to feature papers from Oman, New Zealand, Japan, Bangladesh, China, Vietnam, Japan, and The Philippines. The papers in this collection explore key themes in language education, including the role of technology in learner engagement, teacher autonomy, and leadership in learning communities. It addresses the impact of tools like chatbots and ChatGPT while also focusing on inclusive course design, student-tutor dynamics, and learner readiness for autonomy. Other themes include self-images as motivation for language learning, the emotional and cognitive challenges teachers face in supporting autonomy, and creative methods to understand multilingual experiences. Furthermore, the book review highlights a valuable resource for writing development. Lastly, the ethnographic paper offers interesting insights into learner autonomy in online learning environments.